A systematic study on sustainable low carbon cement – Superplasticizer interaction: Fresh, mechanical, microstructural and durability characteristics - Ishan Bhandari; Rajesh Kumar; A. Sofi; Nikhil Sanjay Nighot (Heliyon, 2023)
As governments around the world take on ambitious construction projects, from housing to infrastructure to transportation, the demand for cement is set to rise. It is anticipated that global cement production is set to achieve a compound annual growth rate of ∼5.1% for the years 2022–2025. The negative impact of cement production on the environment, such as carbon emissions and energy consumption, is also well known. This instigates the need to look for alternative and sustainable supplementary cementitious materials (SCMs) such as Fly ash (FA), Limestone (LS), Metakaolin (MK), Ground granulated blast furnace slag (GGBFS) and Silica fume (SF) which when blended with Portland clinker result in lower carbon emissions and better end products. With expanding cement demand, the need for chemical admixtures has also increased. This comprehensive study focuses on the compatibility of commercially available superplasticizers with SCMs blended low carbon cement and their influence on fresh and hardened properties along with microstructural and durability aspects. The chemistry of superplasticizers and how it effects the hydration mechanism of blended cement are also highlighted in detail. Moreover, the effect of different types of superplasticizers, their dosage, water binder ratio, and details of experiments used by other authors are also discussed and listed. As cementitious matrix containing any kind of SCM such as FA showed better environmental performance on the basis of life cycle assessment which was due to carbon emission factor (ξi). For cement, ξi was 311.27 kg CO2-eq/t, whereas for FA it was much lower (8.70 kg CO2-eq/t). Based on this comprehensive literature review, current challenges for the utilisation of waste SCMs incorporating superplasticizers along with research gap have been identified. Apart from this, the ongoing research work on the effect of chemical and mineral admixture on Limestone-calcined clay cement (LC3) using statistical modelling to optimize the mix is also discussed. It was observed that the use of a specific type of mineral admixture with a superplasticizer inversely affected the mechanical properties like compressive strength and modulus of rupture but improved the water-binder ratio, porosity, and water absorption.